VERTICAL MINERAL ZONALITY OF THE SAN FERNANDO VOLCANOGENIC MASSIVE SULPHIDE DEPOSIT, CUBA - D. De La Nuez Colon (Известия высших учебных заведений: Геология и разведка)
From ten to fifteen percent of the global supply of copper, zinc and lead, as well as a significant amount of silver, gold, cadmium, selenium, tin, bismuth and barium are mined from massive sulphide deposits. Massive sulphide deposits of copper and zinc containing minor lead, gold and silver are located in the region of Central Cuba. These deposits are localised in sedimentary-volcanogenic rocks of the Lower Cretaceous Los Pasos Formation, which are considered the oldest manifestations of magmatism in the island arc of the Caribbean Sea. These deposits include massive sulphide ores and are referred to as volcanogenic massive sulphides (VMS), common among the volcanic deposits of the Greater Antilles. The San Fernando deposit is the most important industrial site featuring stratiform deposits of massive, breccia and disseminated sulphide ores and chalcopyrite-pyrite stockworks localised in the covers and tuffs of rhyolites and dacites. Lenticular ore bodies lie on three levels with an en-echelon overlapping. This article set out to indicate the vertical and lateral mineralogical-geochemical zonality of the San Fernando deposit using 1075 ICP MS analyses of ordinary geochemical samples, a core documentation of 65 exploratory wells and ore microscopy of 146 polished sections. Data for the study was obtained during 2009—2012 exploration work. The main ore bodies of the deposit are lenticular. The relative abundance of chalcopyrite, sphalerite, galena, pyrite, and pyrrhotite was estimated across ore-bearing levels using ore polished sections, which was compared with Cu, Zn, Pb, Cd, Au, and Ag concentrations. An analysis of the data was carried using the QGIS geographic information system. The distribution of copper and zinc-copper ores at the upper level, as well as pyrite ores at the lower level of the deposit, was established. The established geochemical regularities were generally confirmed by the prevalence of the main ore minerals — chalcopyrite and sphalerite. The relatively independent distribution of gold and silver in the Cu and Zn concentration contours indicates possible superimposed processes of noble metalconcentration. According to the conducted mineralogical and chemical analysis, the highest  concentrations of useful components were determined at two depth levels of 60—85 and 125—160 m within the limits of the most productive north-eastern and south-western flanks of the deposit.